Bahasa Indonesia: Bahasa Indonesia - Pramuji Rafli Arrakhman; Wijaya, R. M. Syah Arief Atmaja (JAD : Jurnal Riset Akuntansi & Keuangan Dewantara, 2023)
This research was conducted at the company PT Telkom Indonesia where this company is engaged in telecommunications services and information technology. The purpose of conducting this research is to find out whether the accounting information system in controlling receivables is appropriate or not. The method of data analysis used by the authors in this research is to use qualitative methods where the authors collect data using interview techniques and field observations. The problem that occurs is that there are still obstacles in uncollectible accounts which result in the billing process being late. This makes the payment of bad debts non-current. Some of the risks that occur can be from the company or the customer. The results of the study indicate that the control of receivables has not been carried out properly so that uncollectible trade receivables appear. This study suggests companies to improve accounting information systems to facilitate control of customer invoice due dates.